Implementasi Prinsip Transparansi pada Pengelolaan Dana Desa sebagai Instrumen Ekonomi Pembangunan - Muhammad Aldri Rabbi Radhiyya; Arina Romarina (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Village fund management is a strategic instrument in promoting local economic development. Since the enactment of Law Number 6 of 2014 concerning Villages, village funds have been directly allocated to support various development programs, ranging from infrastructure development to community empowerment and social programs. This study aims to assess the implementation of transparency principles in village fund management and its impact on fund utilization effectiveness and local economic development. The research employs a qualitative descriptive-analytical approach, focusing on official village documents, including financial reports, minutes of village deliberations, and regulations related to fund usage. Document analysis is conducted to identify fund management mechanisms, transparency indicators, fund allocation proportions, and the resulting economic impacts. The results show that villages that consistently apply transparency can enhance the accountability of village officials, active community participation, and the effectiveness of fund utilization. The allocation of village funds for infrastructure development, community empowerment, and social programs contributes positively to improving residents’ welfare, creating employment, and fostering sustainable local economic growth. This study recommends that villages continue to strengthen information disclosure, routinely publish financial reports, involve the community in program planning and monitoring, and conduct regular evaluations of fund utilization. Implementing these recommendations is expected to ensure that village fund management is more targeted, effective, and capable of maximizing economic benefits for local communities.